PENGARUH KUALITAS LAYANAN, PERSEPSI HARGA, KEPERCAYAAN PELANGGAN, DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA HANDAYANI CATERING SEMARANG - Halimah Pudyastuti; Chasanah, Amalia Nur; Sedayu, Agung; Purwatingsih, Aris Puji (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to analyze the effect of service quality, price perception, customer trust, and customer satisfaction on customer loyalty at Handayani Catering Semarang. The study population was Handayani Catering customers in 2022-2024 totaling 190 customers. The sample was determined using purposive sampling method with the criteria of customers who ordered more than once, so that 106 respondents were obtained. Data analysis techniques using multiple linear regression with IBM SPSS software. The results showed that: (1) service quality has a significant positive effect on customer loyalty; (2) price perception has a significant positive effect on customer loyalty; (3) customer trust has a significant positive effect on customer loyalty; and (4) customer satisfaction has a significant positive effect on customer loyalty. The R Square value of 0.757 indicates that 75.7% of the variation in customer loyalty can be explained by the independent variables in this study, while the remaining 24.3% is explained by other variables outside the model.